Socio-demographic factors that impinge social bonding: the case of Malaysian youth - Dahalan, Dzuhailmi; Suandi, Turiman; Hamzah, Azimi; H., Mohammad Rezal; Ismail, Ismi Arif; Hamzah, Siti Raba’ah; Tamam, Ezhar; Ahmad Shah, Wan Mahzom (American-Eurasian Network for Scientific Information, 2011)
Youth is a frequent group that have been put into focus not only in Malaysia even internationally. Youth development issues in Malaysia always get the mass media coverage. Borderless changes in lifestyle in the world give impact to the change of the world’s culture. This results in Malaysian youths to experience cultural change. This cultural change not only affects positive youth development in fact it also make youths as a troubled group. Hence, social bonding approach can help youths to undergo a better and balanced lifestyle. This paper describes a quantitative study on socio-demographic factors selected that influence the social bonding youths in Malaysia. The nine social bonding studied were: 1) spirit of citizenship; 2) family communication quality; 3) quality of communication with teacher and adult; 4) time management pattern; 5) level of healthy habit; 6) attitude on life in multi-racial society; 7) network quality with peer group; 8) level of community involvement; and 9) level of religious practices. The study involved 2538 respondents indicated there were significant differences between socio-demographic factors of gender, race and educational background to the social bonding among the youth. However, socio-demographic factors such as residential areas (urban, small town and rural) and type of house occupied (bungalow, terrace house, apartment and village house) do no have no impact on the difference in social bonding among youth in Malaysia. The findings also shows that the age, parental income and number of siblings has a small but positive correlation to the social bonding of youth.